1986
DOI: 10.1093/nar/14.22.8785
|View full text |Cite
|
Sign up to set email alerts
|

Model for alternative RNA processing in human calcitonin gene expression

Abstract: The alternative RNA processing pathways in human calcitonin gene (CALC-I gene) expression were investigated using steady state RNA isolated from human medullary thyroid carcinoma (MTC) and from a culture line derived from this tumor. On Northern blots the mature 1.0 kilobases (Kb) calcitonin (CT) - and 1.1 Kb calcitonin gene-related peptide (CGRP) mRNAs were detected with CALCI gene specific probes as well as high molecular weight poly (A) containing RNAs of 2.1, 2.3, 3.3, 4.2, 5.0 and 5.7 Kb. The 5.7 Kb RNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…While the term CGRP is widely used, there are actually two forms of this peptide – αCGRP and βCGRP – which are derived from two separate genes. CALCA encodes αCGRP and calcitonin in a tissue‐specific manner and CALCB encodes βCGRP . Other gene products encoded by the CALCA gene include procalcitonin, katacalcin, and N/C‐terminal peptides from pro‐CGRP .…”
Section: What Is Cgrp?supporting
confidence: 62%
“…While the term CGRP is widely used, there are actually two forms of this peptide – αCGRP and βCGRP – which are derived from two separate genes. CALCA encodes αCGRP and calcitonin in a tissue‐specific manner and CALCB encodes βCGRP . Other gene products encoded by the CALCA gene include procalcitonin, katacalcin, and N/C‐terminal peptides from pro‐CGRP .…”
Section: What Is Cgrp?supporting
confidence: 62%
“…In the case of the a-calcitonin/CGRP gene, it was originally proposed that the pattern was regulated at the level of polyadenylation selection . However, it is now clear that the splicing together of the exons generally precedes polyadenylation (Bovenberg et al, 1986).…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%
“…They have also reported that polyadenylation precedes and determines the choice of splicing. Recently Lips' group has confirmed that there is alternative processing, but that polyadenylation at the calcitonin site generally follows the removal of the introns (Bovenberg, van de Meerendonk, Baas, Steenbergh, Lips & Jansz, 1986). Solnick (1985) has reported alternative splicing in vivo and in vitro due to RNA secondary structure.…”
Section: Structural Organization Of the A-calcitonin/calcitonin Gene-mentioning
confidence: 99%